2009
DOI: 10.1124/jpet.109.156513
|View full text |Cite
|
Sign up to set email alerts
|

Increased Sensitivity of GlutathioneS-Transferase P-Null Mice to Cyclophosphamide-Induced Urinary Bladder Toxicity

Abstract: Hemorrhagic cystitis and diffuse inflammation of the bladder, common side effects of cyclophosphamide (CY) treatment, have been linked to the generation of acrolein derived from CY metabolism. Metabolic removal of acrolein involves multiple pathways, which include reduction, oxidation, and conjugation with glutathione. Herein, we tested the hypothesis that glutathione S-transferase P (GSTP), the GST isoform that displays high catalytic efficiency with acrolein, protects against CYinduced urotoxicity by detoxif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 37 publications
3
68
0
Order By: Relevance
“…In an initial study of these animals, Henderson et al (1998) reported that the activity toward CDNB was reduced in lung cytosolic fractions but not in the fractions prepared from the kidney and liver. However, a later study reported reduced activity toward CDNB in cytosolic extracts prepared from liver, lung, and kidney of this same mouse line, with the most dramatic reduction observed in the liver (Conklin et al, 2009). A possible explanation for these disparate findings is the different genetic background of the GSTP-deficient mice.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In an initial study of these animals, Henderson et al (1998) reported that the activity toward CDNB was reduced in lung cytosolic fractions but not in the fractions prepared from the kidney and liver. However, a later study reported reduced activity toward CDNB in cytosolic extracts prepared from liver, lung, and kidney of this same mouse line, with the most dramatic reduction observed in the liver (Conklin et al, 2009). A possible explanation for these disparate findings is the different genetic background of the GSTP-deficient mice.…”
Section: Discussionmentioning
confidence: 77%
“…Mice lacking individual GST genes have provided some functional insight into the role of these enzymes in drug metabolism and risk from environmental carcinogens, especially in the case of GSTP (Henderson et al, 2000;Conklin et al, 2009). However, generating a panel of mice lacking each of the 22 cytosolic mouse GSTs to assess their role in development and normal physiology as well as biotransformation of drugs and xenobiotics would be an arduous undertaking.…”
Section: Introductionmentioning
confidence: 99%
“…Wolf (University of Dundee) and maintained as independent lines for use in this study (16). Similarly, GRX-TG, GRX-null, and matching WT mice were all backcrossed on a B/6 background, and littermates were used as appropriate controls (17).…”
Section: Methodsmentioning
confidence: 99%
“…There is no doubt that the major function of GSTs is to conjugate GSH with electrophilic substrates; however, it was also reported that some GST isoforms possibly play a role in the control of the intracellular signaling pathway (Adler et al, 1999;Dorion et al, 2002). For example, cyclophosphamide-induced nephrotoxicity was potentiated in GSTP-null mice compared with wildtype mice (Conklin et al, 2009). A reactive metabolite of cyclophosphamide conjugated with mercapturic acid, which is derived from its GSH conjugates, was excreted in the urine to the same extent in both types of mice, whereas mitogen-activated protein kinase in bladder was more activated in GSTP-null mice than in wild-type mice.…”
Section: Gst Isoformsmentioning
confidence: 99%